Daya Saing Dinamis Produk Pertanian Indonesia di Asean - Ningsih, Endah Ayu; Kurniawan, Wibowo (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176), 2017)
To win the potential market like ASEAN it is necessary to have a mapping regarding of what products and their competitiveness in each individual market in ASEAN. By utilizing the Dynamic Revealed Comparative Advantage (DRCA) this study focus to analyze the competitiveness of agricultural products in five ASEAN bigest countries namely Malaysia, Thailand, Singapore, the Philippines and Vietnam. This study found that the ASEAN market is very important as an export destination for many Indonesian agricultural products such as live animal; Cereals; Tobacco; milling products; and Cocoa and Cocoa prep. However, Indonesia experienced a decline in the export performance of agricultural products in ASEAN countries due to the emergence of a more competitive competitor. By detailng the analysis in each destination countries, the study found that some Indonesia products still had a high competitiveness in the ASEAN market. In fact, many Indonesian agricultural products increased their competitiveness and were categorized as a rising star product.
Keywords: Dynamic Revealed Comparative Advantage; Agriculture; Indonesia; ASEAN